Internal and external Top Management Team (TMT) networking for advancing firm innovativeness - Mohd Salleh, Sri Sarah Maznah; Fareed, Muhammad; Yusoff, Rushami Zien; Saad, Rohaizah (Index Copernicus Ltd, 2018)
This research is an attempt to examine the influence of TMT networking on firm innovativeness. Firm innovativeness has been the central concern in the upsurge competitive environment. While strategic decisions, such as, innovation has been posited to be potentially derived by the top management team (TMT), network is in fact a vital medium in providing access to different resources which has been found to be a crucial factor contributing to enhanced judgment and decisions. Despite a surge of studies emphasizing the beneficial of networking as well as examining the role of TMT in explaining the firm strategic decision, there is however little empirical research investigating the influence of TMT networking “internal and external“ on firm innovativeness. Therefore, the current study has attempted to fill this gap by surveying 45 TMT leaders representing 45 companies. Findings reveal that TMT internal and external networking has significant impact of firm innovativeness. The study significantly contributes to the Upper Echelon Theory. Further, the study will also benefit the TMT leaders and practitioners as it highlighted the vital contribution of TMT internal and external networking in realizing firm innovativeness.